2000
DOI: 10.1029/2000gl006106
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotopes in scots pine tree rings preserve a record of flow of the river Ob

Abstract: Annual values of carbon isotope ratios for the period 1898–1990 are reported for Scots pine (Pinus sylvestris) growing in the valley of the lower river Ob in western Siberia. The data show highly significant inverse correlation to river flow over the period of instrumental records (1934–1990), although the strength of the relationship shows some dependence on the distance of the tree from the edge of the river. The predictive power of a linear regression model derived from the second half of the data set is va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…This region, like much of the northern high latitudes, is likely to be especially sensitive to warming due to climate change (IPCC, 2007). The classic description of carbon isotope fractionation between plant tissue and the atmosphere (Farquhar et al, 1982(Farquhar et al, , 1989 has been widely used to investigate the physiological response of trees growing within the taiga to climate change (e.g., Robertson et al, 1997;Waterhouse et al, 2000;Buhay et al, 2008;Gagen et al, 2008;Hilasvuori, 2011;Holzk€ amper et al, 2012;Sidorova et al, 2013). Researchers have shown that the d 13 C value measured from successive annual tree-rings reflects changes in the d 13 C value of atmospheric CO 2 (d 13 C CO2 ) and atmospheric CO 2 concentration (pCO 2 ) (McCarroll & Loader, 2004;McCarroll et al, 2009;Schubert & Jahren, 2012) and is modified by changes in stomatal conductance (Warren et al, 2001;Arneth et al, 2002;Leavitt, 2002;McCarroll et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This region, like much of the northern high latitudes, is likely to be especially sensitive to warming due to climate change (IPCC, 2007). The classic description of carbon isotope fractionation between plant tissue and the atmosphere (Farquhar et al, 1982(Farquhar et al, , 1989 has been widely used to investigate the physiological response of trees growing within the taiga to climate change (e.g., Robertson et al, 1997;Waterhouse et al, 2000;Buhay et al, 2008;Gagen et al, 2008;Hilasvuori, 2011;Holzk€ amper et al, 2012;Sidorova et al, 2013). Researchers have shown that the d 13 C value measured from successive annual tree-rings reflects changes in the d 13 C value of atmospheric CO 2 (d 13 C CO2 ) and atmospheric CO 2 concentration (pCO 2 ) (McCarroll & Loader, 2004;McCarroll et al, 2009;Schubert & Jahren, 2012) and is modified by changes in stomatal conductance (Warren et al, 2001;Arneth et al, 2002;Leavitt, 2002;McCarroll et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Tree-ring isotopes, generally in cellulose (see further), are thus potentially useful to reconstruct past climatic conditions with high temporal resolution (Waterhouse et al, 2000;Barbour et al, 2002;Raffalli-Delerce et al, 2004;Danis et al, 2006;Young et al, 2010;Szymczak et al, 2012;Porter et al, 2013). Northeastern Canada is characterized by a very well developed hydrographic network, a heritage of the last glaciation, which constitutes a unique freshwater reserve.…”
Section: Introductionmentioning
confidence: 99%
“…Since the earliest isotopic dendroclimatology studies conducted in the Arctic (Sonninen and Jungner, 1995;McCarroll and Pawellek, 1998;Waterhouse et al, 2000), several isotope studies have made significant contributions to palaeohydrology 5 (e.g. Waterhouse et al, 2000;Holzkämper et al, 2008;2012;Sidorova et al, 2008;Porter et al, 2009).…”
Section: Stable Isotopes In Tree Rings 20mentioning
confidence: 99%
“…Waterhouse et al, 2000;Holzkämper et al, 2008;2012;Sidorova et al, 2008;Porter et al, 2009). The combination of long-lived trees, robust dendrochronologies and excellent sample preservation both on land and in lakes have facilitated the development of several multi-centennial to millennial length isotopic records (Boettger et al, 2003;Kremenetski et al, 2004;Sidorova et al, 2008;Young et al, 2010;Gagen et al, 2011;Loader et al, 2013;Porter et al, 2014).…”
Section: Stable Isotopes In Tree Rings 20mentioning
confidence: 99%
See 1 more Smart Citation